THE ROLE OF GOOD CORPORATE GOVERNANCE ON EARNINGS MANAGEMENT IN INDONESIA - Ria Karina; M. Azza Alfarizi (Universitas Riau Kepulauan, 2021)
This study aims to analyze the effect of implementing good corporate governance in controlling corporate earnings management in companies listed on the Indonesia Stock Exchange (IDX). Earnings management is the dependent variable in this study and the independent variables used in this study are the board of commissioner’s size, the independent board of commissioner’s size, the board of commissioner’s activity, of the audit committee size, the independent audit committee size and the audit firm size. The control variables in this study are audit quality, company size, leverage, and return on assets. This study involved 127 manufacturing companies listed on the Indonesia Stock Exchange in the period 2013 to 2017. The sample selection was carried out using the purposive sampling method. The data used in this study is financial data in annual reports published on www.idx.co.id. The results of this study have proved that the board of commissioner size, independent board of commissioners, audit committee size, audit committee independence and return on asset have significant positive influence on earnings management. Board of commissioner activity, audit firm size, and leverage are able to significantly influence earnings management negatively. Audit quality and company size were not proven to significantly influence earnings management.